The Digital Structuring in MSMEs (Micro, Small and Medium Enterprises) Through the Implementation of QRIS Payments at the University of Jember - Mukhammad Handy Dwi Wijaya; Angga Cahya Febrianto; Oriza Dwi Andhika; Onanong Thippimol (Journal of Southern Sociological Studies, 2025)
Digital transformation in the Micro, Small, and Medium Enterprises (MSMEs) sector or UMKM in Indonesian language, is part of the inclusive development agenda that encourages efficiency and open access to the financial system. One form of this transformation is the implementation of QRIS (Quick Response Code Indonesian Standard) which aims to simplify non-cash transactions in various sectors, including higher education. This article examines the dynamics of digital structuring through a case study of MSME actors in the canteen of the Faculty of Agriculture, University of Jember, who experienced a policy transition from a rental system to a profit-sharing system and were required to use QRIS in all transactions. The approach used was qualitative with a case study method, supported by in-depth interviews and observations, and analyzed using Anthony Giddens' Structuration Theory framework. The results of the study show that the implementation of digital policies did not run completely without obstacles; a number of technical obstacles were found such as the slow QRIS system, limited network infrastructure, and delays in disbursement of funds. However, MSMEs actors demonstrated their capacity as reflective agents who were able to respond to structures through resistance, adaptation, and negotiation. This study concludes that the success of digital structuring is highly dependent on the balance between structural strength and agent reflective power, as well as the need for inclusive and equitable structural support. As part of the Global South context, the implementation of QRIS must truly side with weak groups.